Bovine vaginal strain Kocuria kristinae and its characterization - Styková, Eva; Nemcová, Radomíra; Gancarčíková, Soňa; Valocký, Igor; Lauková, Andrea (Folia microbiologica, 2016)
Kocuria spp. are widely distributed in nature. They are Gram-positive, coagulase-negative, coccoid bacteria belonging to the family Micrococcaceae, suborder Micrococcineae, order Actinomycetales, class Actinobacteria. In general, limited knowledge exists concerning the properties associated with the representants of the genus Kocuria, Kocuria kristinae as well. Following our previous results, K. kristinae Kk2014 Biocenol(™) (CCM 8628) was isolated from vagina of a healthy cow. Its taxonomical allottation was confirmed by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) identification system and phenotypic characteristics. Kk2014 strain showed strong adherence capability to the vaginal mucus, produced organic acids which can play a role in prevention of unsuitable contamination, and showed in vitro antagonistic/antimicrobial activity against strains Arcanobacterium pyogenes CCM 5753, Fusobacterium necrophorum CCM 5982, Streptococcus equi subsp. zooepidemicus CCM 7316, and Gardnerella vaginalis CCM 6221. Antimicrobial activity ranged from 100 to 200 AU/mL, up to 32 mm in size, respectively.
Keywords: zvířata; Gram-Positive Bacterial Infections; vagina; skot; fenotyp; mikrobiální testy citlivosti; Anti-Bacterial Agents; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; bakteriální adheze; grampozitivní bakteriální infekce; Animals; Female; Microbial Sensitivity Tests; spektrometrie hmotnostní - ionizace laserem za účasti matrice; antibakteriální látky; ženské pohlaví; Bacterial Adhesion; Micrococcaceae; Phenotype; Vagina; Cattle